A modular structural operational semantics for delimited continuations - Peter Mosses (WoC 2015: Proceedings of the Workshop on Continuations, 2016)
It has been an open question as to whether the Modular Structural Operational Semantics framework can express the dynamic semantics of call/cc. This paper shows that it can, and furthermore, demonstrates that it can express the more general delimited control operators control and shift.